Motivación y resultados de aprendizaje en Ciencias Naturales. Periodo 2021-2022 - Medina Vélez, Sara Gabriela (2023)
Motivation is a very important element to be taken into account by educators. It has been shown that motivated students present a better academic performance and greater interest in classes. It is necessary to carry out strategies that attract the attention of the students and lead them to get involved in their teaching and learning process. Thus, this research aims to enhance student learning outcomes, through methodological strategies that promote motivation in Natural Sciences in 10th grade "E" of EGB in "Daniel Álvarez Burneo" High School. Throughout the investigative process, the research of various bibliographic sources that support the work has been essential. This research has been carried out through a qualitative, participatory and transversal methodology, supported by the use of techniques such as surveys, interviews and the application of a test; it is qualitative due to the way of processing the information, transversal due to the specific time that it was developed and, it is participatory action-action because it intervened in the reality of the classroom. The intervention was made up of 8 lesson plans through which motivation would be promoted. Among the most important findings, the motivation in the students was determined, with very satisfactory answers in the applied surveys; in addition to an evident increase in the grades of the students obtained in the previous partial. In this way, it is affirmed that motivation is indeed an important factor for students to improve their learning results, which are reflected in their grades; and in this way to get the objectives initially set. Keywords: Motivation, Learning outcomes, EAML Test, Methodological strategies.